Age of Onset and Dominance in the Choice of Subject Anaphoric Devices: Comparing Natives and Near-Natives of Two Null-Subject Languages - Di Domenico, Elisa; Baroncini, Ioli (Frontiers in Psychology, 2019)
Several studies have highlighted the role of cross- linguistic influence in determining the over-use of overt subject pronouns in near- native speakers of a null- subject language as Italian. In this work we inquire on the role of other factors, such as age of onset of exposure and dominance with respect to the choice of subject anaphoric devices in two null-subject languages by bilingual speakers. In order to do so we first single out two languages, Italian and Greek, which do not differ significantly as far as subject anaphoric devices are concerned and instantiate thus a suitable language combination to inquire on the role of relevant factors in bilingual speakers of these two languages, in the absence of cross- linguistic influence related effects (Study 1). In Study 2 we compare the productions in Italian of a group of natives speakers and two groups of near- native speakers: Greek- Italian bilinguals from birth and L2ers of Italian with Greek as an L1. Results reveal that age of onset of exposure to Italian is a relevant factor influencing over- use of overt pronouns: while bilinguals from birth do not differ from native speakers, L2ers over-use overt pronouns compared to both native speakers and bilinguals from birth. In order to establish whether dominance is a possible factor determining bilinguals’ choice of subject anaphoric devices, in Study 3 we compare two groups of Greek- Italian bilinguals from birth: bilinguals living in Greece (dominant in Greek) and bilinguals living in Italy (dominant in Italian). Results reveal no effect of dominance with respect to the production of overt subject pronouns. We found however an unexpected effect in the dominant language of one group: bilinguals living in Greece produce significantly more null pronouns and less lexical DPs in Greek compared to bilinguals living in Italy. We interpret this effect as stemming from the need to differentiate the two languages that these bilingual speakers have to handle in everyday life. Interestingly, this effect is found in the dominant language rather than in the non- dominant one, and does not concern overt pronouns.